2D Layered Material‐Based van der Waals Heterostructures for Optoelectronics. (29th January 2018) - Zhou, Xing; Hu, Xiaozong; Yu, Jing; Liu, Shiyuan; Shu, Zhaowei; Zhang, Qi; Li, Huiqiao; Ma, Ying; Xu, Hua; Zhai, Tianyou
Abstract: Van der Waals heterostructures (vdWHs) based on 2D layered materials with selectable materials properties pave the way to integration at the atomic scale, which may give rise to fresh heterostructures exhibiting absolutely novel physics and versatility. This feature article reviews the state‐of‐the‐art research activities that focus on the 2D vdWHs and their optoelectronic applications. First, the preparation methods such as mechanical transfer and chemical vapor deposition growth are comprehensively outlined. Then, unique energy band alignments generated in 2D vdWHs are introduced. Furthermore, this feature article focuses on the applications in light‐emitting diodes, photodetectors, and optical modulators based on 2D vdWHs with novel constructions and mechanisms. The recently reported novel constructions of the devices are introduced in three primary aspects: light‐emitting diodes (such as single defect light‐emitting diodes, circularly polarized light emission arising from valley polarization), photodetectors (such as photo‐thermionic, tunneling, electrolyte‐gated, and broadband photodetectors), and optical modulators (such as graphene integrated with silicon technology and graphene/hexagonal boron nitride (hBN) heterostructure), which show promising applications in the next‐generation optoelectronics. Finally, the article provides some conclusions and an outlook on the future development in the field. Abstract : van der Waals heterostructures (VdWHs) have experienced a booming development in recent years. In this feature article, preparation methods, electronic and optical properties, and applications in optoelectronics of vdWHs are presented.